2006
DOI: 10.1354/vp.43-2-183
|View full text |Cite
|
Sign up to set email alerts
|

Oleic Acid-associated Bronchiolitis Obliterans-organizing Pneumonia in Beagle Dogs

Abstract: Abstract. Accidental intra-airway exposure of dogs with pure oleic acid produced bronchiolitis obliterans and bronchopneumonia. Pulmonary changes included multifocal to coalescing necrosis of bronchioles and adjacent alveoli, hemorrhage, inflammation, and exudation of fibrin. Hyperplasia of bronchiolar and alveolar epithelial cells and proliferation of loose fibrovascular connective tissue formed polyps or plugs of variable size and shape. Polyps in the airways primarily consisted of fibroblasts with loose or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…Heated soybean oil may itself be a risk factor, in light of recent studies showing the deleterious eVects of oleic acid in the lungs of dogs (Li et al 2006). Oleic and linoleic acid, fatty acids present to a signiWcant degree in soybean oil, have been shown to be respiratory irritants (Khan et al 1991) and have been suggested as models for BOOP and BO in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Heated soybean oil may itself be a risk factor, in light of recent studies showing the deleterious eVects of oleic acid in the lungs of dogs (Li et al 2006). Oleic and linoleic acid, fatty acids present to a signiWcant degree in soybean oil, have been shown to be respiratory irritants (Khan et al 1991) and have been suggested as models for BOOP and BO in humans.…”
Section: Discussionmentioning
confidence: 99%
“…heme oxygenase, nitric oxide synthase) that regulate microvascular dilation and participate in the oxygen burst of reperfusion injury have been shown to induce BOOP changes. (43, 56) These reports imply that the simplest system for studying the development of BOOP may not require alteration of the immune response, but controlled ischemia. The ideal model would reproduce BO reliably, avoid alteration of immune tolerance, affect only one lung, and leave the airways patent.…”
Section: Discussionmentioning
confidence: 99%
“…Experimentally infected dogs with adenovirus [42][43][44], Mycoplasma [45], or cattle clinical infected bovine respiratory syncytial virus pneumonia occasionally develop BOOP [46]. Accidental intra-airway exposure of dog with a noninfectious agent oleic acid also induced BOOP [47]. Majeski at al.…”
Section: Discussionmentioning
confidence: 99%